A covalent organic framework rich in lanthanide Eu3+ binding sites for sensitive and selective determination of tetracycline. (May 2023) - Yao, Ruihong; Deng, Bowen; Li, Zhijian; Xie, Ling; Li, Jin; Tuo, Kai; Fan, Congbin; Pu, Shouzhi
Abstract: Herein, a valid fluorescence sensor using covalent organic framework (COF) coupled with Eu 3+ is built for the detection of TC. Based on the Schiff base reaction, a new covalent organic framework (Bpydah-Tt-COF) rich in N atoms is synthesized by using [2, 2′-bipyridine]-5, 5′-dicarbaldehyde (Bpydah) and 1, 3, 5-triazine-2, 4, 6-triamine (Tt). Since the abundance of N atoms (up to 33.46%) on the skeleton of Bpydah-Tt-COF, more Eu 3+ can facilely anchor on Bpydah-Tt-COF by means of post-modification. Therefore, a Eu 3+ -functioned covalent organic framework (Bpydah-Tt-COF@Eu) is synthesized and used for sensitive detection of TC via "antenna effect". And the detection sensitivity (3.1 nM) and detection range (from 0.08 to 35 μM) for TC by Bpydah-Tt-COF@Eu fluorescence sensor will be significantly improved due to more target analytes can be identified by Eu 3+ on the Bpydah-Tt-COF@Eu. Besides, the Bpydah-Tt-COF@Eu fluorescence sensor has been successfully utilized for TC monitoring in actual samples with good precision (RSD<1.98%) and recoveries (99.89–105.1%). Graphical abstract: Based on the Schiff base reaction, a new covalent organic framework (Bpydah-Tt-COF) rich in N atoms was synthesized by using [2, 2′-bipyridine]-5, 5′-dicarbaldehyde (Bpydah) and 1, 3, 5-triazine-2, 4, 6-triamine (Tt). Thanks to the abundant binding sites (bipyridine N, imine bind, triazine N) in the skeleton of Bpydah-Tt-COF, the Eu 3+ can be easily grafted onto the Bpydah-Tt-COF skeleton by means of post-modification. Under the excitation wavelength at 375 nm, tetracycline (TC) can coordinate with the coordination unsaturated Eu 3+ on Bpydah-Tt-COF and TC can efficiently sensitize the Eu 3+ based on antenna eﬀect (AE). Image 1 Highlights: A novel and sensitive fluorescence sensor based on N-rich COF@Eu was constructed. The proposed sensor realized a rapid, highly sensitive and selective for detection of TC. The proposed sensor showed a satisfactory result on detection of TC in real samples.